PENGARUH KOMPETENSI GURU TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMAN 1 TAMBUN SELATAN - Muhammad Nurkholik; Nahuda; Ibrahim; Husheini Fadhil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of teacher competence on student learning outcomes (a survey study at SMAN 1 Tambun Selatan) through the collection of valid, objective, and reliable data. This research is motivated by the importance of teacher competence, particularly pedagogical competence, in creating an effective learning process that can improve student learning outcomes. This study employed a descriptive-analytical method with a quantitative approach. The research population consisted of all eleventh-grade students at SMAN 1 Tambun Selatan, while the research sample was determined using the sampling technique established in the study. Data were collected using a Likert-scale questionnaire to measure the Teacher Competence variable (X) and the Student Learning Outcomes variable (Y). The results of the study, based on the Product Moment correlation coefficient test, showed an rxy or ro value of 0.613, indicating that ro was greater than rt at the 10% significance level (0.1707). Comparing the values of rxy and rt, the obtained rxy was 0.613, while rt was 0.1707. Thus, rxy > rt at the 10% significance level, indicating that the Alternative Hypothesis (Ha) was accepted, while the Null Hypothesis (Ho) was rejected. This means that there is an effect of teacher competence on student learning outcomes, with the strength of the effect falling into the moderate category.